(untitled) (European Journal of Natural Sciences and Medicine, 2022)
This article examines the health status of the population in Bulgaria at age 65 by gender during the period 2006-2014. The health status is examined by some of the most frequently used demographic indicators, namely life expectancy, based on mortality data and healthy life years and healthy life expectancy, based on mortality, life expectancy and self-perceived health. The main results show that despite of the observed increase in life expectancy at age 65 in Bulgaria during the period it is the lowest compared to other European countries. The share for both men and women reported their health status as without limitations in respect to daily activities decline, while those reported their health status as good increase. These contradictory facts reflect on the measures of health status. Thus, the trend in healthy life years for both sexes decline over the period, whereas the trend in healthy life expectancy increases. Compared with the other European countries, the expected number of years without limitations in Bulgaria is among the largest, while the healthy life expectancy is the lowest. These differences could be explained by the different levels in mortality and the nature of the measures of health status themselves.